2021
DOI: 10.1089/jpm.2019.0667
|View full text |Cite
|
Sign up to set email alerts
|

Goal-Concordant Care in the Era of Advanced Stroke Therapies

Abstract: Stroke is a leading cause of disability and mortality worldwide. Recent advances in stroke care now enable patients with severe ischemic stroke owing to large vessel occlusion to safely undergo endovascular thrombectomy (EVT) up to 24 hours since their time of last known well, with the goal of improving functional outcomes by recanalization of the occluded vessel and reperfusion of downstream ischemic brain tissue. The objective of this analysis is to highlight clinical and ethical challenges related to ensuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Care consistent with the patient's goals of care is known as goal-concordant care. 7 One method proposed to prevent the provision of non-goal-concordant care, or unwanted treatment, is advance care planning (ACP). Litzelman et al 8 found that ACP facilitated by trained community health workers, among U. S. HH patients with dementia who were already frequent users of acute care, was associated with a reduction in using acute care services.…”
Section: Introductionmentioning
confidence: 99%
“…Care consistent with the patient's goals of care is known as goal-concordant care. 7 One method proposed to prevent the provision of non-goal-concordant care, or unwanted treatment, is advance care planning (ACP). Litzelman et al 8 found that ACP facilitated by trained community health workers, among U. S. HH patients with dementia who were already frequent users of acute care, was associated with a reduction in using acute care services.…”
Section: Introductionmentioning
confidence: 99%
“…16,18,19 Recently, the potential impact of the expanded time window for advanced stroke treatment on goal-concordant care has been reviewed. 20 Most patients in this study were enrolled before the expansion of the endovascular treatment time window to 24 hours and, therefore, it is unlikely that these considerations impacted our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Shared decision-making is central to high-quality healthcare but stroke brings additional challenges to patient participation including sudden illness, impaired communication, lack of capacity, and proxy (substitute) decision-making. 13 , 30 The devastating impact of severe stroke on the lives of patients and families globally is evident. 31 Both decision making and quality of life evolve over a stroke illness trajectory so measures for patients and proxy (substitute) decision-makers suited to early and later phases were highlighted by our panelists and key stakeholders.…”
Section: Discussionmentioning
confidence: 99%